Some Fishy Things About Scales: Macro- and Micro-approaches to Later Prehistoric and Romano-British Field Systems. (June 2013) - Chadwick, Adrian
Abstract : Abstract : In British archaeology, there are apparent tensions between macro-level, landscape-wide analyses, and micro-level, site-based approaches. Macro-level analyses are based on techniques and technologies such as aerial photograph transcriptions, LiDAR data and GIS-based mapping, as exemplified in many excellent National Mapping Programme studies and several new large-scale research projects. These studies have proved invaluable in mapping extensive areas of archaeology, and GIS-based data can be interrogated through many forms of spatial analysis. At the same time, developer-funded fieldwork has provided opportunities to excavate and record large areas thus contributing a significant amount of new information to field system studies at a detailed, localised level or micro-scale. This difference between scales is explored through a series of case studies focusing on later prehistoric and Romano-British field systems. Different approaches and methodological, temporal and interpretative scales are examined, and the creative rather than negative aspects of such tensions are explored.